Equivalence of almost root vectors of polynomial beams of operators - Radzievsky , G. V. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
The equivalence of derived chains constructed from the principal vectors of polynomial sheafs of operators acting in Hilbert space is studied. These derived chains correspond to different boundary-value problems on the semi-axis for operator-differential equations whose symbol is these operator sheafs. On the basis of equivalence tests assertions are deduced concerning the minimality of derived chains corresponding to a boundary-value problem on the semi-axis in the case in which the initial conditions of the vector solution at zero are known, and the solution itself obeys radiation-type conditions at infinity.